Adverse Effects of Oral Nonselective and cyclooxygenase-2-Selective NSAIDs on Hospitalization for Acute Kidney Injury: A Nested Case–Control Cohort Study. Issue 9 (March 2016) - Chou, Chia-I.; Shih, Chia-Jen; Chen, Yung-Tai; Ou, Shuo-Ming; Yang, Chih-Yu; Kuo, Shu-Chen; Chu, Dachen
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: To investigate the association between the use of nonselective or cyclooxygenase (COX)-2-selective nonsteroidal antiinflammatory drugs (NSAIDs) and risk of acute kidney injury (AKI) in a general Asian population. We conducted an observational, nationwide, nested case–control cohort study using Taiwan's National Health Insurance Research Database between 2010 and 2012. AKI cases were defined as hospitalization with a principle diagnosis of AKI. Each case was matched to 4 randomly selected controls based on age, sex, and the month and year of cohort entry. Odds ratios (ORs) were used to demonstrate the association between hospitalization for AKI and current, recent, or past use of an oral NSAID. During the study period, we identified 6199 patients with AKI and 24, 796 matched controls. Overall, current users (adjusted OR 2.73, 95% confidence interval [CI] 2.28–3.28) and recent users (adjusted OR 1.17, 95% CI 1.01–1.35) were associated with increased risk of hospitalization for AKI. The risk was also similar for nonselective NSAIDs. However, neither current nor recent use of COX-2 inhibitors was significantly associated with AKI events. Our study supported that the initiation of nonselective NSAIDs rather than COX-2 inhibitors is associated with an increased risk of AKI requiring hospitalization. Future randomized trials are needed to elucidate these findings.